2010
DOI: 10.1111/j.1365-2966.2010.17286.x
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent pair cascades in magnetospheres of neutron stars - I. Dynamics of the polar cap cascade with no particle supply from the neutron star surface

Abstract: I argue that the problem of electromagnetically driven electron–positron cascades in magnetospheres of neutron stars must be addressed starting from first principles. I describe a general numerical algorithm for doing self‐consistent kinetic simulations of electron–positron cascades – wherein particle acceleration, pair creation and screening of the electric field are calculated simultaneously – and apply it to model the Ruderman & Sutherland cascade in one dimension. I find that pair creation is quite regular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 49 publications
13
142
0
Order By: Relevance
“…The calculations took into account particle acceleration, pair creation and screening of the electric field by newly created pairs. Timokhin (2010) found that the backstreaming particles would be responsible for heating of the polar cap to temperature T s ∼ 4 × 10 6 f −0.25 K, where (R dp /c) f is the time between two successive discharges. According to the calculations of the cohesive energy (Medin & Lai 2007) for such a high temper- (c) Figure 9.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations took into account particle acceleration, pair creation and screening of the electric field by newly created pairs. Timokhin (2010) found that the backstreaming particles would be responsible for heating of the polar cap to temperature T s ∼ 4 × 10 6 f −0.25 K, where (R dp /c) f is the time between two successive discharges. According to the calculations of the cohesive energy (Medin & Lai 2007) for such a high temper- (c) Figure 9.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the accompanying paper (Szary et al 2014a) we apply the PSG model to explain the radio emission of magnetars. Timokhin (2010) applied the model of Ruderman & Sutherland (1975) to one dimensional self-consistent kinetic simulations of electron-positron cascades. The calculations took into account particle acceleration, pair creation and screening of the electric field by newly created pairs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…These steady-state cascades yield pair multiplicities up to 10 4 [73] that are a strong function of pulsar period and surface magnetic-field strength. However, recent studies of time-dependent polar-cap pair cascades [149,150] . Pplar view of the current density distributions (current density j relative to the Goldreich-Julian current density jGJ) on the polar cap in a force-free magnetosphere for different pulsar inclination angles α B .…”
Section: Pair Cascadesmentioning
confidence: 99%
“…However, the process of the pair creation is expected to be highly non-stationary (see, e.g., Levinson et al 2005;Timokhin 2010 for theoretic and numerical considerations of the pair creation in vacuum gaps, respectively), thus even if anelectric-field-free state of themagnetosphere is possible, it cannot be stable (Sturrock 1971). The gaps, i.e., regions in whichthe charge density isnot sufficient for the electric field screening, may appear sporadically in the magnetosphere, for example, in the vicinity of the stagnation surface, i.e., at the boundary that separates acretion and ejection trends in the flow.…”
Section: The Magnetospheric Modelmentioning
confidence: 99%